Home » Aptitude » Algebra » Question
  1. If ab + bc + ca = 0, then the value of
    1
    +
    1
    +
    1
    is
    ( a² - bc )( b² - ac )( c² - ab )

    1. 2
    2. –1
    3. 0
    4. 1
Correct Option: C

ab + bc + ca = 0
⇒ ab + ca = – bc
∴ a2 – bc = a2 + ab + ca
⇒ a2 – bc = a (a + b + c)
Similarly,
b2 – ac = b (a + b + c)
c2 – ab = c (a + b + c)

∴ Expression =
1
+
1
+
1
( a² - bc )( b² - ac )( c² - ab )

Expression =
1
+
1
+
1
a (a + b + c)b (a + b + c)c (a + b + c)

Expression =
bc + ac + ab
= 0    { ∴ ab + bc + ca = 0 }
abc (a + b + c)



Your comments will be displayed only after manual approval.